Mass balance and economic study of a treatment chain for nickel, cobalt and rare earth elements recovery from Ni-MH batteries - Otron, Aba Marie Anne-Antoine (Environmental technology, 2024)
The aim of this project is to develop and evaluate the economic performance of a complete process for recovering nickel, cobalt, and rare earths (REEs) from nickel metal hydride (Ni-MH) battery waste. The main elements contained in the battery powder are Ni (523 g/kg), La (58 g/kg), Co (39 g/kg), Zn (21 g/kg), Nd (19 g/kg), Sm (19 g/kg) and Ce (14 g/kg). Metal leaching was carried out with 2 M sulfuric acid, solubilising 100% of Ni, 93% of Co and 94% of REEs. Rare earths were precipitated with NaOH, then purified after resolubilization in nitric acid. Solvent extraction with bis(2-ethylhexyl) phosphoric acid (D2EHPA) followed by bis(2,4,4-trimethylpentyl) phosphinic acid (Cyanex 272) was used to separate Ni and Co. At the end of the process, REEs, nickel, and cobalt were recovered as oxides after precipitation as oxalates. The REE, nickel and cobalt oxides obtained have purities of 97.6%, 97.2% and 93.2% respectively. A techno-economic study was carried out using SuperPro Designer software. In this scenario, plant capacity was set at 1.0 t of used battery powder per hour for an operating period of 8 h/d and 250 days per year. The total investment was estimated at $26.9 million, with a payback period of 1.58 years. For a 15-year life, the net present value of this project is estimated at $95.9 million, with an interest rate of 7%. The internal rate of return is estimated at 46.1%, which is considered acceptable and economically viable